Understanding the christian message in Venda : a study of the traditional concepts of God and of life hereafter among the Venda, with reference to the impact of these concepts on the christian churches - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2009.